THE HARMONY OF DIGITAL TECHNOLOGIES AND UZBEK CULTURE IN MODERN EDUCATION (American Journal of Interdisciplinary Research and Development, 2025)
This article highlights the importance of integrating digital technologies into modern education while emphasizing the necessity of preserving Uzbek culture and values. In the era of globalization, the effective use of digital tools enhances the quality of education, yet it is equally crucial to pass down our national traditions and cultural heritage to the younger generation. Practical suggestions are provided for promoting culture through digital technologies and preserving the Uzbek language, literature, and traditions in the educational process.